Home health care - Elias, Jaan, (SAGE Business cases., 2020)
Blue Wolf Capital Partners was making major investments in the home health care sector. The private equity fund had purchased two U.S. regional companies in the space - NHHC (National Home Health Care Corporation), announced in November 2015, and GLC (Great Lakes Caring Home Health and Hospice), announced in May 2016, with an investment reported as $104 million. The plan was to merge the two organizations, creating opportunities for shared expertise and synergies in reducing management costs.